PERNIKAHAN DINI : LATAR SOSIAL, IMPLIKASI DAN ALTERNATIF SOLUSI - HIDAYATULLAH, MUH SAFRANI (Ikatan Hakim Indonesia (IKAHI), 2024)
This field research which takes place in the Central Lombok district with the title Early Marriage, Social Background, Implications, focuses on the social background of the phenomenon of the practice of early marriage as a result of the dominance of the granting of marriage dispensation applications at the Praya Religious Court as one of the large contributors in the Mataram Religious High Court area, in addition to seeing the implications and finding alternative solutions to prevent it. Through a socio-empirical approach, data from observations, (applicants and children of marriage dispensation, leaders and judges as respondents) were using qualitative methods. The results of the analysis show that PA. Praya in the last 3 years granted more than 90% of Marriage Dispensation applications, the aspect of avoiding adultery (90%) is the main reason for submission, personal desire (40%) dominant factor of parents marrying minors and the occurrence of household disharmony (34%) is the dominant impact. The alternative research strategies are Optimising Children's Capacity, Creating a Conducive Environment for Child Marriage Prevention, Accessibility and Strengthening Services, Strengthening Regulations and Institutions Strengthening Stakeholder Coordination. The role and support of families, communities, educational institutions the government through strengthening and ensuring regulations the most appropriate strategy to prevent underage marriage as the best conclusion and suggestion in this study.